Modelling & Simulation of Three-phase Induction Motor Fed by an asymmetrically Configured Hybrid Multilevel Inverter (International Journal of Engineering and Computer Science, 2013)
Multilevel inverters (MLIs) have become viable solution for high power DC-AC conversion. They are especially advantageous for induction motors because of low dv/dt stress and low common mode voltages. Quality of a multilevel waveform is enhanced by increasing the number of levels. However, for increased number of levels, component count becomes very high. In this paper an asymmetrically configured hybrid inverter is employed for a three-phase induction motor, resulting in low device count as compared to the classical topologies. MATLAB/Simulink based models are used to simulate and validate the proposed concepts. .